Who Guards the Guard? The Need for Meta-Evaluation of Higher Education Quality Assurance Agencies in Namibia - lipumbu, Nangula; Shawa, Lester Brian (International Journal of African Higher Education, 2021)
Meta-evaluations by Quality Assurance Agencies (QAAs) aim to evaluate the quality of the evaluators of quality assurance. While such evaluations are the norm, especially in Europe, they are rare in Africa. A critical literature review was conducted to ascertain whether meta-evaluations were conducted in Namibia. The study estab- -lished that such evaluations have yet to be practiced in the country. Drawing on Clark’s model of the organisa- -tional analysis of higher education institutions and the higher education system as an analytical lens, and based on the African Standards and Guidelines for Quality Assurance and some cases of meta-evaluation by QAAs, we argue for the need to conduct such evaluations in Namibia. The article provides an overview of QAAs’ operations and functions, as well as the current external quality assurance system for higher education in Namibia and justifies the necessity of meta-evaluation in the Namibian context in order to enhance the capacity of QAAs and the quality of higher education institutions. Key words: Higher Education, meta-evaluation, Namibia, quality assurance, Quality Assurance Agencies